Alih Kode Dan Campur Kode Dalam Video Youtube Nessie Judge - Hanum Citra Nasution; Lisnawati Sitorus; Hasan Adlani Tanjung; Marsela Naomi Sirait; Frinawaty Lestarina Barus; Emasta Evayanti Simanjuntak (Pusat Riset dan Inovasi Nasional, 2023)
The purpose of this study is to describe the forms of code switching and code mixing that occur in Nessie Judge's YouTube videos. This research method uses a qualitative descriptive method. The data collection technique in this study was the listening technique and the note taking technique, namely by listening and observing the contents of Nessie Judge's YouTube videos and then noting the forms of code switching and code mixing that occurred. The source of this research data comes from one of Nessie Judge's YouTube videos. In this study, data analysis techniques included re-reading video transcripts, recording conversations involving code-mixing and code-switching, and drawing conclusions. The results of this study indicate that there are 19 data in the form of code switching and 20 data in the form of code mixing. Code switching and code mixing are caused by speakers and speech partners who are both able to use more than two languages.